2015
DOI: 10.1159/000375132
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Single Metachronous Liver Metastases from Breast Cancer Stage I-II Yield Excellent Overall and Disease-Free Survival. Single Center Experience and Review of the Literature

Abstract: Purpose: Improved survival after liver resection for breast cancer liver metastases (BCLM) has been proven; however, there is still controversy on predictive factors influencing outcomes. The analysis of factors related to primary and metastatic cancer eventually influencing long-term outcomes and a review of the literature are presented in this report. Methods: Twenty-seven patients diagnosed with metachronous BCLM between 1996 and 2013 were retrospectively reviewed. Patients who had a minimum disease-free in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In contrast to the substantial evidence for local treatment of colorectal liver metastases, the data for resection of BCLM are limited. In heterogenous case series the reported median 3-, and 5-year survival rates after metastasectomy of BCLM range between 24–116 months, and 49–94% and 5–78%, respectively [3,10,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. In a systematic review Fairhurst et al [55] analyzed 33 papers dealing with resection of BCLM in a total of 956 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the substantial evidence for local treatment of colorectal liver metastases, the data for resection of BCLM are limited. In heterogenous case series the reported median 3-, and 5-year survival rates after metastasectomy of BCLM range between 24–116 months, and 49–94% and 5–78%, respectively [3,10,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]. In a systematic review Fairhurst et al [55] analyzed 33 papers dealing with resection of BCLM in a total of 956 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In order to select the proper patients, it is crucial to find out independent factors that influence the prognosis after BCLM resection. Characteristics of primary breast cancer such as small tumor size, low grade, node negativity, and early stage may be associated with better outcome after liver metastasectomy [39,40,41,58]. Moreover, response to preoperative systemic therapy has been identified as a prognostic factor which is likely related to effective systemic eradication of microscopic metastatic lesions [3,21,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two selection criteria for patients to be accepted for curative hepatic resection are, first, the absence of extrahepatic disease (with the exception of isolated pulmonary and bony metastases) and, second, the ability of the surgeon to perform an R0 resection with a low risk of morbidity [ 11 ]. Furthermore, solitary liver metastasis is a significant prognostic factor [ 12 14 ]. Preoperative detailed exploration using multislice CT, contrast-enhanced MRI, or PET scan should be mandatory to minimize unnecessary surgery and maximize survival benefit.…”
Section: Case Presentationmentioning
confidence: 99%
“…Several studies have found that patients with ER- and/or PgR-positive BCLM are good candidates for liver metastasectomy due to favorable tumor biology and administration of hormone therapy [ 13 , 15 ]. Such characteristics of primary breast cancer as small tumor size, node negativity, low grade and early stage may also be associated with better outcome after liver metastasectomy [ 9 , 13 , 14 ]. On the other hand, patients with triple negative phenotype in the primary breast cancer and/or liver metastases may not benefit from liver metastasectomy due to aggressive biological behavior and limited treatment strategies.…”
Section: Case Presentationmentioning
confidence: 99%